IBM: Cost of a Data Breach Report. Issue 8 (August 2021) - Unknown
Abstract : This is the 17th edition of the annual 'Cost of a Data Breach Report' and things aren't getting any better. The number of breaches climbs every day and the impact from them is becoming more devastating. It's almost as if we're not trying.